Inelastic Behavior of Materials and Structures Under Monotonic and Cyclic Loading - Altenbach, Holm; Brünig, Michael (Springer eBooks, 2015)
This book presents studies on the inelastic behavior of materials and structures under monotonic and cyclic loads. It focuses on the description of new effects like purely thermal cycles or cases of non-trivial damages. The various models are based on different approaches and methods and scaling aspects are taken into account. In addition to purely phenomenological models, the book also presents mechanisms-based approaches. It includes contributions written by leading authors from a host of different countries.